Mitigating Anthropogenic Pressures on Sea Turtle Conservation Ecotourism: A DPSIR Analysis at Kili-Kili Beach, Trenggalek - Dinda Lufi Novitasari; Ardyanto Tanjung (Peneliti.net, 2026)
Sea turtle conservation ecotourism at Kili-Kili Beach (PTKK), Trenggalek, faces dual sustainability challenges stemming from high tourism potential and coastal geo-hazards. This study aims to analyze sustainability dynamics using the DPSIR framework (Driving-Pressure-State- Impact-Response) and assess community disaster resilience using the Hazard-Vulnerability- Capacity (HVC) framework to formulate structured mitigation strategies. The research employed a descriptive qualitative method through in-depth analysis, evaluating suitability indices (IKW: 84.93%; IKH: 77.77%) and primary data from interviews with the Community Watch Group (POKMASWAS) and area managers. DPSIR results showed a critical conflict where IKW exceeds IKH, driven mainly by educational tourism and weekend visits controlled by strict Village Regulations. Although POKMASWAS achieved highly effective local success (95% hatching rate), systemic decline (population decrease since 2013) suggests pressures beyond local management. HVC analysis highlighted high Vulnerability to Tsunami (near the Austroasian Trench) and Abrasion, exacerbated by residential areas being flat with sea level and the lack of structural Early Warning Systems (EWS). Mitigation capacity is strong in Eco-DRR (mangrove and pandanus planting), favored over expensive Giant Sea Walls, but weakened by reliance on signs and daytime WhatsApp communication for tsunamis. Therefore, a transformation is necessary: shifting from reactive management to data-based coastal landscape management using 60 biodiversity inventory points, formalizing Ecologically Essential Area (KEE) zoning, and strengthening POKMASWAS institutional capacity to reduce anthropogenic risk and build holistic resilience.